Secure Mobile Computing via Public Terminals - Sharp, Richard; Scott, James; Beresford, Alastair R. (Proceedings of the 4th International Conference on Pervasive Computing (Pervasive 2006), 2006)
The rich interaction capabilities of public terminals can make them more convenient to use than small personal devices, such as smart phones. However, the use of public terminals to handle ersonal data may compromise privacy. We present a system that enables users to access their applications and data securely using a combination of public terminals and a more trusted, personal device. Our system (i) provides users with capabilities to censor the public terminal display, so that it does not show private data; (ii) filters input events coming from the public terminal, so that maliciously injected keyboard/pointer events do not compromise privacy; and (iii) enables users to view personal information and perform data-entry via their personal device. A key feature of our system is that it works with unmodifed applications. A prototype implementation of the system has been publicly released for Linux and Windows. The results arising from a pilot usability study based on this implementation are presented.